Pendidikan Islam Multikultural diSekolah - Dwiyani, Aryanti (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This paper examines the problem of multicultural Islamic education in public schools byprioritizing religious, cultural and social values in schools, students can have anunderstanding of religion, diversity and differences in life. The importance of multiculturalIslamic education is taught in public schools, especially in the era of globalization marked byadvances in science and technology that have had a positive impact on life. However, on theother hand, this progress has had a negative impact on the lives of students. The occurrence ofexclusive attitudes and a lack of understanding of differences, diversity, tolerance andmoderation of religions, including understanding religious values in the lives of students,causes multicultural values in schools to fade and disappear. The methodology used is observation, interviews and documentation and is supported by various relevant references sothat it has scientific value in research. This paper attempts to provide an offer or solution